Do Urbanization, Remittances, and Globalization Matter for Energy Consumption in Belt and Road Countries: Evidence From Renewable and Non-Renewable Energy Consumption - Zhao, Lijin; Qamruzzaman, Md. (Frontiers in Environmental Science, 2022)
Energy–growth nexus has gained immense interest among researchers, policymakers, and academicians, and with conclusive evidence, it is revealed that sustainable economic growth significantly relies on energy availability and security. Another line of studies postulated that excessive fossil fuel application had created adversity for environmental degradation and ecological imbalance. However, the energy demand from renewable and non-renewable has intensified with the act of several macro-fundaments, and countries have been investing efforts to figure them out in energy policy formulation; thus, BRI (please see Appendix A) are not out of the trend. The motivation of the study was to explore the role of urbanization, remittances, and globalization in energy consumption in BRI nations for the period 2004–2020. A panel of 59 (fifty-nine) BRI nations has been considered a sample countries’ assessment and their selection purely depended on the data availability. Several panel data estimation techniques have been applied, including CIPS and CADF, for panel unit root test, cointegration test with error correction, dynamic seemingly unrelated regression, and Dumitrescu–Hurlin panel heterogeneous causality test. The coefficient of globalization has exposed negative (positive) and statistically significant ties with non-renewable (renewable) energy consumption, whereas remittances and urbanization revealed positive and significant associations with both renewable and non-renewable energy consumption. The directional causality test documented bidirectional causality between globalization and renewable energy consumption and urbanization, globalization, and remittances to non-renewable energy consumption.